Writing Ukraine - Kostash, Myrna (Athabasca University Press, 2024)
Myrna Kostash’s term as writer in residence at Athabasca University began shortly after the escalation of the Russo-Ukrainian War in 2022. In this essay, based on her writer-in-residence lecture at Athabasca University, Kostash offers a self-critical reflection on her body of work and considers how her visits to Ukraine and the ongoing war have nuanced her writing about and understanding of Ukrainian Canadian identity.